Entrepreneurial behaviour and agribusiness potentials in the mushroom industry in Sri Lanka - Kuruppu, I.V.; Fernando, S.P.; Silva, L.D.S.D.; Hapuarachchi, H.A.H.J. (Colombo Economic Journal, 2023)
The study aims to explore the present status of the mushroom industry and the entrepreneurial behaviour of mushroom farmers in Sri Lanka. It was conducted across six districts in Sri Lanka using a sample of 289 respondents. Multi-stage random sampling was used in the study. Pre-tested structured questionnaire survey, Key Informant Interviews, Focus Group Discussions, and case study analysis were used to derive data. Entrepreneurial Behaviour Index (EBI) and the level of entrepreneurship for each component were also used. Results revealed that nearly three fourth of the respondents demonstrated relatively lower scores for all components: innovativeness, farm decision making, achievement motivation, farmer entrepreneurship, risk taking ability, planning ability, leadership ability and cosmo-politeness. The highest EBI was found in achievement motivation whilst the lowest in risk taking ability. Findings propose need for suitable strategies to enhance the entrepreneurship capacity of farmer-entrepreneurs in the industry.
Keywords: Alternative income; Agribusiness; Entrepreneurial behaviour index; Mushroom industry; Rural economy; Value addition